A Decision-Making Model for Kindergarten School Selection Using the AHP Method: A Case Study of West Bekasi - Novita Indriyani; Ahmad Fauzi; Andika Bayu Hasta Yanto (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Choosing a Kindergarten (TK) is an important decision for parents because it involves many aspects such as the quality of educators, curriculum, facilities, costs, and environmental safety. However, the complexity of these criteria often creates uncertainty in making objective decisions. This study applies the Analytical Hierarchy Process (AHP) method to help provide recommendations for selecting the best kindergarten in the West Bekasi area. The hierarchical structure is built with six main criteria assessed by respondents through pairwise comparisons using Expert Choice. The synthesis results show that Kindergarten C received the highest weight of 0.433, followed by other alternatives, thus being determined as the best choice based on the criteria used. A Consistency Ratio (CR) value of 0.1 indicates that respondents' assessments are within the consistent limit (CR ≤ 0.1). Thus, the AHP model is proven to be able to measure priorities in a structured manner and help parents in making decisions about choosing a kindergarten more objectively and rationally.